Protection of Trademark Rights from the Perspective of MUI Fatwa Number: 1/MUNAS/VII/MUI/5/2005 (Case Study of Mie Gacoan and Mie Gacok) - Nabila Yasmine Al Khanis; M. Amar Adly (Dinasti International Journal of Education Management And Social Science, 2024)
Imitation of the nomenclature of Mie Gacoan by Daun Kipas Café and Resto located in Langsa City with the name Mie Gacok along with imitation of its logo is a violation of trademark rights which is a violation of intellectual property rights. The imitation struggles to take advantage unilaterally. In this study, the author formulates the problem, namely how the conflict of trademark rights imitated between mie gacok and mie gacoan, legal protection of intellectual property rights in trademarks, and protection of trademark rights perspective Fatwa MUI Number: 1/MUNAS/VII/MUI/5/2005. This research uses empirical legal research methods somewhat easier for researchers in analyzing cases in the field. The results of the study proved that infringement of intellectual property rights on trademarks. This is considered an administrative criminal act that should be able to be pursued legally. In addition, according to MUI fatwa No. 1/MUNAS VII/MUI/15/2005 concerning Protection of Intellectual Property Rights, the actions of Gacok noodle owners against Gacoan noodles are acts that violate the provisions of MUI No. 1/MUNAS VII/MUI/15/2005 concerning Protection of Intellectual Property Rights which are illegal acts. In addition, MUI fatwa No. 1/MUNAS VII/MUI/15/2005 concerning Protection of Intellectual Property Rights is preventive protective and cannot protect repressively if it does not go hand in hand with Law Number 15 of 2001 concerning Trademarks and Law Number 28 of 2014 concerning Intellectual Property Rights.